Plan von Fort Cumberland auf der insel St. Laurenti. - Coltz, C., cartographer. (William L. Clements Library Image Bank, 1760)
Relief shown pictorially.; Pen and ink, watercolor plan of an island fort with medieval architecture.; Possibly a depiction which confuses Fort Cumberland, formerly Fort Beauséjour, on the Chignecto Isthmus, with Fort Louisbourg on Cape Breton Island, Nova Scotia.; Includes table of reference to buildings.; Not in Brun.